EVALUATION OF SENSITIVITY TO CLOPIDOGREL: THE CURRENT STATE OF THE PROBLEM - A. L. Komarov («REMEDIUM GROUP» Ltd., 2015)
The review deals with the laboratory assessment of clopidogrel effect in patients with CHD. The article presents the results of major studies that have demonstrated the relationship between the residual platelet reactivity level and drug pharmacogenetics abnormalities causing coronary complications. It discusses proposals of the international expert organizations on the assessment of sensitivity to clopidogrel and possible modifications of antiplatelet treatment.